ANALISIS HUBUNGAN PENGUASAAN LAHAN DAN POLA BAGI HASIL DENGAN TINGKAT KEMISKINAN PETANI PENGGARAP - Muhammad Faisal; Abdul Halim (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2022)
This study aims to analyze the relationship between land tenure and profit sharing patterns with the povertylevel smallholder farmers using a quantitative approach. Data obtained by questionnaire. The respondentswere 396 farmers who were taken by proportionate random sampling technique. Data analysis using SPSSapplication version 23. Test the hypothesis with Spearman Rank statistics. There is a significant relationshipbetween land tenure and profit sharing patterns with poverty levels. With the current land tenure and productionsharing patterns, it turns out that most of the tenants in Maros Regency are vulnerable to poverty. For thisreason, it is necessary to have regulations and policies that enable these vulnerable poor tenants not to becomepoor with the use of available land, as well as mutually beneficial profit sharing schemes between land ownersand smallholders.